Twinkle and Chubbins: their astonishing adventures in nature-fairyland - Baum, L. Frank; Barney, Maginel Wright; Reilly & Britton Co. (Reilly & Britton Co., 1911)
Twinkle, with her friend Chubbins, explore the world around Edgeley, South Dakota where they meet many animals and learn many things from them.
This first and only edition of this rare L. Frank Baum book, reprints all 6 of the Twinkle Tales that first appeared in 1906. The illustrator is Frank Lloyd Wright's sister.
Mr. Woodchuck -- Bandit Jim Crow -- Prairie-dog town -- Prince Mud-Turtle -- Twinkle's enchantment -- Sugar-loaf mountain.
Twinkle, with her friend Chubbins, explore the world around Edgeley, South Dakota where they meet many animals and learn many things from them.
Keywords: Friendship / Juvenile fiction.; Conduct of life / Juvenile fiction.; Children / Conduct of life / Juvenile fiction.; Animals / Juvenile fiction.; Animal welfare / Juvenile fiction.; Natural history.; Edgeley (N.D.) / Juvenile fiction.; Dust jackets (Binding) / 1911 / rbbin; Fantasy literature. / 1911 / rbgenr; Fantasy fiction. / gsafd